Enhancing Carriers’ Confinement by Introducing BAlGaN Quantum Barriers for the Better Optoelectronic Performance of Deep UV LEDs - Jamshad Bashir; Muhammad Usman; Dmitri Sergeevich Arteev; Zoya Noor; Ahmed Ali (Photonics)
Ultraviolet light-emitting diodes (LEDs) based on Aluminum Gallium Nitride (AlGaN) suffer from poor carriers’ confinement effect, one possible solution to this problem is to increase the barrier heights for carriers by increasing Aluminum content in quantum barriers (QBs), which results in a higher turn-on voltage. Keeping this in mind, we have improved the carriers’ confinement by introducing a small amount of Boron nitride (BN) (2%) in ternary QBs and an electron injecting layer, which results in higher barriers that restrict the out-of-active region movement of electrons and holes. With quaternary BxAlyGazN QBs, significantly enhanced electrons and hole concentrations can be observed in the active region of quantum wells (QWs), which leads to a 4.3 times increased radiative recombination rate with a 68% better internal quantum efficiency (IQE) than the referenced conventional LEDs. Relying on the fairly improved IQE and radiative recombinations, other optoelectronic characteristics such as luminous power, emission intensity, etc., are also enhanced. Our whole analysis is based on numerical techniques but we believe that fabricating the proposed type of LEDs will result in desirable light extraction and external quantum efficiencies.